Expunging Board of Pharmacy Disciplinary Actions - Alex Adams; Timothy P. Frost (University of Minnesota Libraries Publishing, 2023)
Boards of pharmacy have the authority to discipline licensees whose actions fall short of practice standards. Disciplinary action may include license suspension, revocation, practice restrictions, fines and reprimands. Once discipline is levied against a board of pharmacy licensee, it is usually part of the licensee's permanent record. At least four states have created a pathway for individuals to seek expungement of previous disciplinary actions levied by a board of pharmacy. These states have variations on what violations may be expunged and when. Given the evolving approach to the regulation of pharmacists, more states may want to consider expungement pathways in the years ahead.